Community-Based Early Warning System Model for Stream Overflow In Barranquilla - Serna-Galeano, Iván Andrés Felipe; Gómez-Vargas, Ernesto; Camargo-López , Julián Rolando (Ingeniería, 2024)
Context: This work aims to design and create a community-based early warning model as an alternative for the mitigation of disasters caused by stream overflow in Barranquilla (Colombia). This model is based on contributions from social networks, which are consulted through their API and filtered according to their location. Methods: With the information collected, cleaning and debugging are performed. Then, through natural language processing techniques, the texts are tokenized and vectorized, aiming to find the vector similarity between the processed texts and thus generating a classification. Results: The texts classified as dealing with stream overflow are processed again to obtain a location or assign a default one, in order to for them to be georeferenced in a map that allows associating the risk zone and visualizing it in a web application to monitor and reduce the potential damage to the population. Conclusions: Three classification algorithms were selected (random forest, extra trees, and k-neighbors) to determine the best classifier. These three algorithms exhibited the best performance and R2 regarding the data processed in the regressions. These algorithms were trained, with the k-neighbor algorithm exhibiting the best performance.